A Precursor to Solar Prominence Eruptions: Detection and Analysis of EUV Prominence Oscillations - William Beckwith-Chandler; Claire Foullon; Erwin Verwichte (The Astrophysical Journal, 2024)
The eruption of prominences can have a significant influence on the solar–terrestrial environment. However, accurately predicting these eruptions remains a challenge. We apply automated detection methods for extreme ultraviolet (EUV) prominences observed by the twin spacecraft from the Solar Terrestrial Relations Observatory (STEREO) mission and the Solar Dynamics Observatory near Earth. We study an event, during 2011 March, when each STEREO spacecraft is in quadrature with respect to the Earth. For two time ranges, we obtain longitudinal height profiles as a function of time. We also track the corresponding EUV filaments across the solar disk, which reveal the emergence of ultra-long-period oscillations in the EUV filament channels. Our analysis shows a correlation between the prominence’s increasing height and the oscillation periods, suggesting a potential link to the subsequent eruption observed by the STEREO spacecraft off-limb. These findings offer new insights into prominence dynamics and may pave the way for improved eruption prediction.